2022
DOI: 10.1002/adhm.202200045
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation Strategies for the Successful Regeneration of a Tissue‐Engineered Vascular Graft

Abstract: Cardiovascular disease leads to the highest morbidity worldwide. There is an urgent need to solve the lack of a viable arterial graft for patients requiring coronary artery bypass surgery. The current gold standard is to use the patient's own blood vessel, such as a saphenous vein graft. However, some patients do not have appropriate vessels to use because of systemic disease or secondary surgery. On the other hand, there is no commercially available synthetic vascular graft available on the market for small d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 114 publications
0
26
0
Order By: Relevance
“…16 They release high levels of PDGF that can stabilize the vascular cells and regulate deposition of extracellular matrix and graft remodeling. 47 In this study, macrophages had a high viability which did not show differences between the textile and hydrogel components of the composite vascular graft. After 7 days of in vitro culture, the composite vascular graft enhanced the activation of macrophages, evidenced by upregulating both M1-related genes, TNF-a and IL-1b, and M2-related genes, STAT6 and IL-10.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…16 They release high levels of PDGF that can stabilize the vascular cells and regulate deposition of extracellular matrix and graft remodeling. 47 In this study, macrophages had a high viability which did not show differences between the textile and hydrogel components of the composite vascular graft. After 7 days of in vitro culture, the composite vascular graft enhanced the activation of macrophages, evidenced by upregulating both M1-related genes, TNF-a and IL-1b, and M2-related genes, STAT6 and IL-10.…”
Section: Discussionmentioning
confidence: 52%
“…Encapsulating immunomodulatory cytokines in the hydrogel matrix could potentially alter the macrophage phenotype toward promoting vascular regeneration. 47,48,59,68,69 Optimizing the pore size and stiffness of the hydrogel matrix for macrophage response and vascular regeneration could also be important. Garg et al previously indicated that the pore size of an electrospun polydioxanone mesh could alter macrophage gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplementary Figure S1 , the pore diameters of the inner surfaces of all scaffolds are similar, <10 μm, which is able to support the growth of the cells ( Saksena et al, 2016 ; Lv et al, 2018 ). However, the bulk structure of the scaffolds, like pores and porosity, will influence the nutrient circulation, vessel formation, and regulation of inflammation ( Feng et al, 2011 ; Wang et al, 2020 ; Zhang and King, 2022 ; Stahl et al, 2023 ). Among scaffolds PP19-PP91, PP46 exhibits the largest pores in the bulk (cross section, Supplementary Figure S1A4 ) of 32.48 ± 6.51 μm and the highest porosity at 85.48 ± 3.90% ( Figures 2Aa–c ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages are the main response cells in the early stage after biomaterial implantation, which have different phenotypes and are classified into M1 and M2 types ( Zhang and King, 2022 ). M1 macrophages, also known as pro-inflammatory macrophages, secrete pro-inflammatory cytokines such as IL-1β, tumor necrosis factor alpha and IL-6, etc ( Sheikh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%